Understanding the Size Selectivity of Redfish (Sebastes spp.) in North Atlantic Trawl Codends - Herrmann, Bent; Sistiaga, Manu Berrondo; Nielsen, Kåre Nolde; Larsen, Roger B. (Journal of Northwest Atlantic Fishery Science, 2012)
The majority of trawl selectivity studies for the three redfish species of particular commercial importance in North Atlantic fisheries: Sebastes marinus, Sebastes mentella and Sebastes fasciatus, are based on data collected from diamond mesh codends with mesh sizes ranging from 88 mm to 147 mm. We demonstrate how results from these studies can be understood by morphological characteristics of the species. We predict codend size selection based on morphological data collected from golden redfish (S. marinus) individuals. Further, consistent with previously reported morphological similarities between the three redfish species, we show the predictions for S. marinus may successfully be extrapolated to understand experimental codend size selectivity results reported for S. mentella and S. fasciatus. In addition to the comparison with previously reported data, we present new experimental results for a codend applied in Northeast Atlantic redfish trawl fishery.